Novel EDAS++ method: Interval type criteria and extension to EDAS+ - Štilić, Anđelka (The Business of Tourism, 2020)
Multicriteria problems belong to poorly structured decision-making problems as they take place in conditions of stochasticity (indeterminacy). This primarily refers to the number of criteria and the complexity of their mutual relations between which there may be complete opposition, as well as to the methodologically diverse space for determining preferences or weighting factors which significantly affect the decision-making results.The paper focuses on the introduction of new types of criteria: 1 - 4 interval  type criteria and its implementation in EDAS + method of multicriteria analysis.
Keywords: criteria; interval type criteria; EDAS; weighting factor; optimization